Diagnostic value of serum survivin, Ki-67 and thymidine kinase in dogs with nasal cavity disease - Sarah Rösch; Annkathrin Estaller; Gerhard Ulrich Oechtering; Stephan Neumann (Frontiers in Veterinary Science)
BackgroundThe most common nasal cavity disease (ND) in dogs is the malignant nasal cavity tumor. Prognosis and survival after radiation therapy are reported to correlate with tumor size, and therefore indirectly with the time to diagnosis. Diagnosis of a nasal tumor requires imaging procedures under anesthesia. Thus, diagnostic serum markers are urgently needed for early detection and for therapeutic monitoring.Materials and methodsThis prospective, blinded study included dogs with nasal discharge that completed a comprehensive diagnostic workup for ND. Dogs were evaluated by blood testing and whole-body CT and those with concomitant diseases or with steroid pre-treatment were excluded. Serum survivin, Ki-67, and thymidine kinase 1 (TK1) concentrations were determined, and the survivin-lymphocyte ratio (SLR) calculated. Results were compared between groups of dogs with different NDs and to ten healthy controls.ResultsA total of 55 dogs were included, consisting of 25 with malignant ND (12 sarcomas, 13 carcinomas) and 30 with benign ND (7 benign tumors, 13 dogs with idiopathic rhinitis (IR), 10 others including dogs with dental diseases and sinonasal aspergillosis). Survivin and SLR were significantly increased in dogs with malignant ND and in subgroup comparison in sarcomas compared to controls. In addition, the SLR was significantly increased in carcinomas and IR compared to controls. In dogs with IR, no differences were observed in survivin concentrations or SLR based on microbiological or histopathological findings. Survivin concentrations or SLR in dogs with nasal tumors were not significantly different between T-categories. No significant differences were detected in TK1 concentrations among the groups, nor in Ki-67, except for significantly lower Ki-67 concentrations in benign tumors compared to carcinomas and the group others including, e.g., dental diseases.ConclusionAlthough not diagnostic for ND, increased survivin serum concentrations or SLR can be detected in dogs with malignant nasal tumors and IR. In malignant nasal tumors, survivin and SLR did not correlate with tumor size and therefore may be useful in the detection of even small nasal tumors. Therefore, in dogs with nasal tumors and IR, survivin and SLR could serve as a target for disease monitoring or as therapeutic target.